How Employee Competency and Self Efficacy Affect Employee Work Engagement in Human Resource Development Agency (BPSDM) Ministry of Law and Human Rights Republic of Indonesia - Ari Anggarani Winadi Prasetyoning Tyas; Syarifuddin Tippe; Slamet Sutanto (IJHCM (International Journal of Human Capital Management), 2020)
Human Resources Development Agency (BPSDM) Ministry of Law and Human Rights Republic of Indonesia is a supporting agency in the Ministry of Law and Human Rights which is in charge of developing human resources in the field of law and human rights. As a supporting unit for the main task of BPSDM, the Ministry of Law and Human Rights of Republic of Indonesia improves the quality of law and human rights apparatus to be professional and have a high level of engagement to provide excellent service. This study aims to analyse the effect of employee competence on employee work engagement mediated by self efficacy in Human Resoruces Development Agency (BPSDM) Ministry of Law and Human Rights Republic of Indonesia. The study involved 221 employee respondents at BPSDM Ministry of Law and Human Rights Republic of Indonesia for group III. Analysis of the data was using the LISREL Structural Equation Modelling of self-efficacy and employee engagement. The results showed that employee competency and self efficacy respectively have positive and significant direct effects on employee work engagement. Employee competency has a positive and significant direct effect on self efficacy, and employee competency has a positive and significant indirect effect on employee work engagement mediated by self efficacy. Implications of the results of this study, BPSDM Ministry of Law and Human Rights Republic of Indonesia needs to develop employee competency attributes that can improve self-efficacy. This needs to be done given that self-efficacy will affect the degree of engagement of BPSDM employees to the Indonesian Ministry of Law and Human Rights.